El reloj de las pruebas diagnósticas (2003)
ABSTRACT: This article intends to show that describers on old and modern diagnostic tests belong to a same structure. The means for such an effect is a circle (clock) that provides a global vision of these in a dichotomous scene. By using of the set theory, we form nine subgroups, that is: the internal validity (V), the clinical yield (R), and that of prevalences (P), and those of homologous (A and B), opposite (C and D), and complementary elements (E and F). Among the clock components, we establish similarities, differences, and the opposite duality principle, and the complementary principle are stated. Consequently, new indices are created and the modern concepts of positive and negative likelihood ratios are compared with two of them. As a result, indices form a much more comprehensible structure thanks to the diagnostic clock. Which, becomes a visual means to extract the Bayesians equations, and whose analysis arises a method which, according to the exposed principles, helps to deduce these Bayesians equations, and another type of formulas (dual ones).